Transformasi Budaya Akademik Melalui Program International Baccalaureate: Studi di SMP Al-Hikmah International Boarding School Malang - Nayla Rizqi Amaliya; Syafa Ratu Aziza; Safira Rahma Putri; Alfin Izzul Haq; Shobihatul Fitroh Noviyanti (Al-Kindi, 2026)
This study explores the transformation of academic culture through the implementation of the International Baccalaureate (IB) program at SMP Al-Hikmah International Islamic Boarding School Malang. The study aims to understand how IB influences students’ learning behaviors, teacher strategies, and the integration of local and Islamic values. A qualitative descriptive approach was employed, involving semi-structured interviews with two students, a vice principal, and a technology teacher, as well as participatory observations and school documentation. Findings indicate that the IB program encourages self-managed learning, active student engagement, reflective thinking, and collaborative skills. Teachers adapt their teaching methods to facilitate student-centered learning, using flexible classroom arrangements, technology, and continuous guidance to support students’ autonomy. Integration of local Islamic values is applied through structured modules, religious discussions, and visual learning media. Collaboration with external institutions further strengthens students’ leadership, independence, and character development. Overall, the study demonstrates that combining international curriculum standards with local and religious values can create a learning culture that is independent, reflective, and adaptive, preparing students for global challenges. The findings provide practical insights for educational institutions seeking to implement international curricula while preserving cultural and religious identity, and suggest areas for future research on broader student populations and long-term outcomes.